Factors influencing University of Papua New Guinea medical imaging science students considering rural radiography careers - Ruth Pape; Kelly Spuur; Jenny Wilkinson (James Cook University, 2023)
Introduction: The aim of this research was to explore factors influencing students at the University of Papua New Guinea (UPNG) Bachelor of Medical Imaging Science (BMIS) choice to pursue rural radiography careers.Methods: A survey and focus groups of BMIS students at the UPNG were undertaken. The survey included questions related to sociodemographic variables including gender, age, education, rural background and previous employment; and Likert-type scale questions exploring motivation for rural practice, the promotion of radiography through rural practice and the influence of birthplace and incentives to practice. Focus groups comprising convenience samples of six students each from the second, third and fourth years of study explored the promotion of rural radiography, community-based training internships, the benefits of rural practice and the influence of undergraduate training on future rural practice.Results: There were 54 responses (94.7%) to the survey with strong interest (88.9%) in rural radiography practice; 96.3% (n=52) agreed that undergraduate rural training would also act as a motivator. Rural training was a stronger incentive for females than for males (p=0.02). Not being trained in conventional non-digital film screen imaging at UPNG was a strong barrier to rural practice; while being able to give back to the community, increased professional responsibility, cheaper living, job satisfaction and cultural exchange were all viewed as positive aspects of rural practice. Most students reported a benefit to rural practice, while acknowledging a lack of contemporary imaging equipment in rural facilities.Conclusion: The study demonstrated that UPNG BMIS students would contemplate careers in rural practice and provides evidence to support dedicated undergraduate rural radiography placement. It also highlights the dichotomy in urban and rural services, which suggests the need for greater emphasis on conventional non-digital film screen radiography in the undergraduate program to best support graduates to work and, importantly, work effectively in rural communities. As most students were from rural areas these results must be tempered by the fact that students may simply be wanting to return home rather than reporting explicit rural intent. A more comprehensive study of the medical imaging profession in PNG should be undertaken to validate this study. Keywords: developing countries, diagnostic imaging, health services, healthcare workforce, Papua New Guinea, professional practice location, radiography, rural health services, workforce.